Implications of the GC-HARMS Fishermen's Citizen Science Network: Issues Raised, Lessons Learned, and Next Steps for the Network and Citizen Science. (February 2019) - Sullivan, John; Croisant, Sharon; Howarth, Marilyn; Subra, Wilma; Orr, Marylee; Elferink, Cornelis
This paper is intended to complement our extended documentation and analysis of the activities of the Gulf Coast Health Alliance: Health Risks related to the Macondo Spill project Community Outreach and Dissemination Core entitled, "Building and maintaining a citizen science network with fishermen and fishing communities after the Deepwater Horizon oil disaster using a Community-Based Participatory Research (CBPR) approach." We discuss nuances of CBPR practice, including trust-building, clarification of stakeholder expectations, balancing timelines and agendas, cultural fluency, and the importance of regional history—political-economic context, regulatory practices, and cultural life-ways—in creating social dynamics that overarch and underpin the entire process. We examine the unique role of knowledge-making hybrid structures like the project's Fishermen's citizen science network and compare/contrast this structure with other models of participatory science or deliberation. Finally, we reiterate the importance of environmental health literacy efforts, summarize project outcomes, and offer thoughts on the future roles of collaborative efforts among communities and institutional science in environmental public health.